(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Education for peace is a social necessity for coexistence. The culture of peace is the set of values, attitudes and behaviors that reflect respect for life, dignity and human rights (Jiménez-Bautista, 2008). Schools are affected by situations of violence, by misinformation on a culture of peace, particularly in schools on the periphery. This descriptive study aims to identify the level of knowledge of the culture of peace concept. Using surveys of parents and teachers of two elementary schools in a vulnerable context. The results show the ignorance of the parents in education for peace and that their children have suffered some type of violence within the school. Teachers show little access to programs for the prevention of school violence, due to the meager dissemination of the protocol, little understanding and only administrative implementations that cause little education in the culture of peace, since the protocols are actions isolated from the problem in question. .